Clinical cases of measles in pregnant women - Riabokon, O. V.; Izbytska, N. H.; Bilokobyla, S. O.; Onishchenko, T. Ye.; Riabokon, Yu. Yu.; Рябоконь, Олена Вячеславівна; Ізбицька, Ніна Григорівна; Білокобила, Світлана Олександрівна; Оніщенко, Тетяна Євгенівна; Рябоконь, Юрій Юрійович; Рябоконь, Е. В.; Избицкая, Н. Г.; et al. (Запорізький державний медичний університет, 2020)
The aim of the work is to analyze the clinical course of measles in hospitalized pregnant women for the period of 2017–2019 years. Materials and methods. The clinical course of measles was analyzed in 4 pregnant patients with this disease aged from 19 to 30 years, who were hospitalized in the Regional Infectious Clinical Hospital during 2017–2019 years. The diagnosis of measles was established according to the WHO criteria (2013). All pregnant women with measles had epidemiological history of contact with measles patients and in all cases diagnosis of measles was confirmed by detection measles IgM in the Zaporizhzhia Regional Laboratory Center of the Ministry of Health of Ukraine. Results. It was found that in all pregnant women who were included in the study, measles developed in the third trimester of pregnancy, one patient was pregnant with twins. The development of measles was accompanied by the appearance of typical clinical symptoms with formation of moderate (n = 2) and severe (n = 2) course. One pregnant woman had never been vaccinated against measles during her lifetime; other three patients had no documented evidence of previous measles vaccination. Most of the pregnant women (3 out of 4) had complications of measles from respiratory system: acute bronchitis (n = 1), acute bronchitis with pulmonary edema and respiratory failure of I–II degree (n = 1), community-acquired lower lobe right-sided pneumonia, left lung atelectasis, respiratory failure of III degree (n = 1). Only in one 26-year-old pregnant measles had moderate course without complications. In two pregnant women development of complications needed treatment in the intensive care unit. In 30-year-old pregnant woman with twins with gestational age of 27–28 weeks from the first day of the rash, complications like measles enteritis appeared, and from the second day of the rash there were signs of acute respiratory failure due to development of pulmonary edema. On the background of complex medical treatment with use of oxygen therapy, patient recovered, pregnancy progressed without complications. However, in one unvaccinated 25-year-old woman, who had not been vaccinated with measles, severe course of the disease was accompanied not only by the development of complications, but also had adverse effects on pregnancy. In this patient, measles was complicated by community-acquired right-sided pneumonia of group IV, left lung atelectasis, acute respiratory failure degree III, toxic-hypoxic encephalopathy and brain edema, which required mechanical ventilation. In addition, chronic hepatitis C was first diagnosed. Against this background, there was premature birth within 30 weeks. Conclusions. According to analysis of four observations we can determine that measles in pregnancy has both moderate and severe course, but development of complications from respiratory system was recorded in the majority of patients (3 out of 4 patients). In severe cases of measles in pregnant women treatment in the intensive care unit was required due to development of pulmonary edema on the background of acute bronchitis in combination with measles enteritis (n = 1), community-acquired right-sided pneumonia in combination with left lung atelectasis (n = 1). The above clinical observation demonstrates the development of a very severe complicated course of measles in previously unvaccinated 25-year-old pregnant, which led to premature birth in the gestation period of 30 weeks.

Мета роботи – проаналізувати клінічний перебіг кору у госпіталізованих вагітних за період 2017–2019 рр. Матеріали та методи. Проаналізували клінічний перебіг кору у 4 вагітних віком від 19 до 30 років. Пацієнтки госпіталізовані в Обласну інфекційну клінічну лікарню протягом 2017–2019 рр. Діагноз кору встановили за критеріями ВООЗ (2013). Усі вагітні, які хворі на кір, мали дані епідеміологічного анамнезу щодо контакту з хворими на кір; у всіх випадках діагноз кору був підтверджений виявленням IgM до вірусу кору в «Запорізькому обласному лабораторному центрі МОЗ України». Результати. Встановили, що в усіх вагітних, які були залучені в дослідження, кір розвинувся в третьому триместрі вагітності, одна пацієнтка була вагітна двійнею. Розвиток кору супроводжувався появою типової клінічної симптоматики кору з формуванням середньотяжкого (n = 2) i тяжкого (n = 2) перебігу. Одна вагітна протягом життя жодного разу не була щеплена проти кору, інші 3 пацієнтки не мали документального підтвердження попередньої вакцинації проти кору. У більшості вагітних (3 із 4) виявили ускладнення кору з боку респіраторної системи: гострий бронхіт (n = 1), гострий бронхіт із набряком легень і дихальною недостатністю I–II ступеня (n = 1), позагоспітальна правобічна нижньодольова пневмонія, ателектаз лівої легені, дихальна недостатність III ступеня (n = 1). Тільки в однієї вагітної віком 26 років кір мав середньотяжкий перебіг без ускладнень. Двоє вагітних унаслідок розвитку ускладнень потребували лікування в реанімаційному відділенні. У вагітної двійнею віком 30 років із терміном гестації 27–28 тижнів із першого дня висипки з’явилися ознаки такого ускладнення, як ентерит, а з другого дня висипки – ознаки гострої дихальної недостатності внаслідок розвитку набряку легень. На тлі комплексного медикаментозного лікування із застосуванням оксигенотерапії пацієнтка одужала, вагітність перебігала без ускладнень. Але в однієї нещепленої раніше проти кору пацієнтки віком 25 років тяжкий перебіг кору не лише супроводжувався розвитком ускладнень, але й мав несприятливі наслідки на перебіг вагітності. У цієї пацієнтки кір ускладнився позагоспітальною правосторонньою пневмонією IV групи, ателектазом лівої легені, гострою дихальною недостатністю III ступеня, токсико-гіпоксичною енцефалопатією, набряком головного мозку, що потребувало проведення штучної вентиляції легень. До того ж у неї вперше діагностували хронічний гепатит С. На цьому тлі відбулися передчасні пологи в термін 30 тижнів. Висновки. За даними аналізу 4 спостережень можна стверджувати: кір у вагітних має і середньотяжкий, і тяжкий перебіг, але розвиток ускладнень з боку респіраторної системи зареєстрували в більшості хворих (3 із 4). При тяжкому перебігу кору вагітні потребували лікування в реанімаційному відділенні внаслідок розвитку набряку легень на тлі гострого бронхіту в комбінації з коровим ентеритом (n = 1), позагоспітальної пневмонії справа в поєднанні з ателектазом лівої легені (n = 1). Наведене клінічне спостереження демонструє розвиток украй тяжкого ускладненого перебігу кору в нещепленої раніше вагітної віком 25 років, що призвело до передчасних пологів у термін гестації 30 тижнів.

Цель работы – проанализировать клиническое течение кори у госпитализированных беременных за период 2017–2019 гг. Материалы и методы. Проанализировали клиническое течение кори у 4 беременных в возрасте от 19 до 30 лет. Женщины госпитализированы в Областную инфекционную клиническую больницу в течение 2017–2019 гг. Диагноз кори устанавливали согласно критериям ВОЗ (2013). Все беременные, больные корью, имели данные эпидемиологического анамнеза контакта с больными корью. Во всех случаях диагноз кори подтвержден обнаружением IgM к вирусу кори в «Запорожском областном лабораторном центре Министерства здравоохранения Украины». Результаты. Установлено, что у всех беременных, которые включены в исследование, корь развилась в ІІІ триместре беременности, одна пациентка была беременна двойней. Развитие кори сопровождалось появлением типичной клинической симптоматики с формированием среднетяжелого (n = 2) и тяжелого (n = 2) течения. Одна беременная за всю жизнь ни разу не была привита против кори, остальные 3 пациентки не имели документального подтверждения ранее проведенной вакцинации против кори. У большинства беременных (3 из 4) отмечены осложнения кори со стороны дыхательной системы: острый бронхит (n = 1), острый бронхит с отеком легких и дыхательной недостаточностью I–II степени (n = 1), внегоспитальная правосторонняя нижнедолевая пневмония, ателектаз левого легкого, дыхательная недостаточность III степени (n = 1). Только у одной беременной в возрасте 26 лет корь имела среднетяжелое течение без осложнений. Двое беременных вследствие развития осложнений нуждались в лечении в реанимационном отделении. У беременной двойней в возрасте 30 лет со сроком гестации 27–28 недель с первого дня сыпи появились признаки такого осложнения, как энтерит, а со второго дня сыпи – признаки острой дыхательной недостаточности в результате развития отека легких. На фоне комплексного медикаментозного лечения с применением оксигенотерапии пациентка выздоровела, беременность протекала без осложнений. У одной непривитой ранее против кори пациентки в возрасте 25 лет тяжелое течение кори не только сопровождалось развитием осложнений, но и имело неблагоприятные последствия на течение беременности. У этой пациентки корь осложнилась внегоспитальной правосторонней пневмонией IV группы, ателектазом левого легкого, острой дыхательной недостаточностью III степени, токсико-гипоксической энцефалопатией, отеком головного мозга, что требовало проведения искусственной вентиляции легких. К тому же у нее впервые диагностирован хронический гепатит С. На этом фоне произошли преждевременные роды в сроке 30 недель. Выводы. По данным четырех наблюдений можно отметить, что корь у беременных имеет и среднетяжелое, и тяжелое течение, однако развитие осложнений со стороны дыхательной системы зарегистрировано у большинства больных (3 из 4). При тяжелом течении кори беременные нуждались в лечении в реанимационном отделении вследствие развития отека легких на фоне острого бронхита в сочетании с коревым энтеритом (n = 1), внегоспитальной пневмонии справа в сочетании с ателектазом левого легкого (n = 1). Приведенное клиническое наблюдение демонстрирует развитие крайне тяжелого осложненного течения кори у непривитой ранее беременной в возрасте 25 лет, что привело к преждевременным родам в сроке гестации 30 недель.
Клінічні випадки кору у вагітних
Клинические случаи кори у беременных
Keywords: measles in pregnant women; clinic; complications; кір у вагітних; клініка; ускладнення; корь у беременных; клиника; осложнения